Frequency and Antibiogram of Streptococcus spp Isolated from Different Specimens: Three years of study: Streptococcus spp Isolated from Different Specimens - Assafi, Mahde Saleh (Cellular and Molecular Biology, 2023)
Streptococcus is involved in mild and severe infections with a high level of antimicrobial resistance. This study aimed to investigate the prevalence and multi-drug resistance of Streptococcus spp isolates for three years (2016, 2017, and 2018). 1648 participants (246 males and 1402 females) were enrolled. Specimens were collected and transferred to the laboratory. All isolates were examined and identified according to standard methods. Susceptibility to antibiotics was evaluated utilizing the method of disk diffusion. Overall, Streptococcus spp were confirmed in 124 (7.52%) patients. The UTIs rate was significantly higher (76.6%) compared with other infections. The infected females were considerably higher than the infected males, 64.5% and 12.1% respectively. Higher percentages of Streptococcus spp were observed in 2017 (41.3%). The frequency of Streptococcus was higher in January compared with other months of the year. Streptococcus spp and S. pyogenes dominated over these months. The highest frequency of Streptococcus spp was found in age groups 16-20 and 21-25 (22/18.49%, and 26/21.85% respectively). Multi-drug resistance was found among 36 (81%) of Streptococcus pyogenes, 50% (5/10) of Streptococcus viridans and 75% of Streptococcus faecalis. The overall Streptococcus spp showed 90 (72.6%) multi-drug resistance. High resistance was recorded to different antibiotics, Ceftazidime (96.6%), Oxacillin (96.7%) and Cefixime (86.9%). The incidence of Streptococcus spp was high during the three years of study with high resistance to the most available antibiotics. Susceptibility testing should be carried out and the empirical antibiotic treatment should be altered accordingly.